1996
DOI: 10.1016/s0741-5214(96)70143-x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the incidence of deep venous thrombosis in hospitalized children

Abstract: The development of acute DVT in children is unusual. As a result, DVT prophylaxis and screening is unnecessary in young children with only two risk factors for the development of the disease. Young age appears to be an important protective risk factor for the prevention of DVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 19 publications
0
25
1
1
Order By: Relevance
“…4 Most episodes occur in association with known risk factors such as malignancy, surgery or thrombophilic states. 2,4 The differential diagnosis of an acutely swollen limb is long. In this example, the initial diagnosis of DVT was missed in this child because of its rarity as well as the lack of recognised risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Most episodes occur in association with known risk factors such as malignancy, surgery or thrombophilic states. 2,4 The differential diagnosis of an acutely swollen limb is long. In this example, the initial diagnosis of DVT was missed in this child because of its rarity as well as the lack of recognised risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2] Its occurrence usually suggests an inherited or acquired hypercoagulable state. Mechanical obstruction and prolonged immobility such as during air travel have been shown to predispose to DVT in adults, 3 but never before in children.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Rohrer et al [57] found an incidence of lower extremity DVT of only 0.05% (1 of 93 cases, in a 17-year-old) in hospitalized children with at least two independent risk factors for thrombosis. A study of pediatric intensive care unit patients found 4% to have DVT [58], whereas at autopsy the rate of PE in children was approximately 4% [59].…”
Section: Specific Patient Populationsmentioning
confidence: 99%
“…1,2 It has been estimated that the yearly incidence of deep venous thrombosis (DVT) is as high as 250 000 cases in the United States alone [3][4][5] and as many as 100 000 patients die annually from pulmonary embolism (PE). 6 In addition to early risk of PE, late morbidity may develop from recurrent thrombosis and the postthrombotic syndrome.…”
mentioning
confidence: 99%